2021
DOI: 10.3389/fmicb.2021.726409
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning Techniques to an Agent-Based Model of Pantoea

Abstract: Agent-based modeling (ABM) is a powerful simulation technique which describes a complex dynamic system based on its interacting constituent entities. While the flexibility of ABM enables broad application, the complexity of real-world models demands intensive computing resources and computational time; however, a metamodel may be constructed to gain insight at less computational expense. Here, we developed a model in NetLogo to describe the growth of a microbial population consisting of Pantoea. We applied 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In this study, we employed an ML emulator to conduct sensitivity analysis. Emulators are useful in approximating the relationship between inputs and outputs of simulations to reduce computational intensity of sensitivity analysis (Chen et al, 2021; Ligmann‐Zielinska et al, 2020). To approximate our simulation model, we used linear, ridge, and lasso regression models to fit the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we employed an ML emulator to conduct sensitivity analysis. Emulators are useful in approximating the relationship between inputs and outputs of simulations to reduce computational intensity of sensitivity analysis (Chen et al, 2021; Ligmann‐Zielinska et al, 2020). To approximate our simulation model, we used linear, ridge, and lasso regression models to fit the results.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analysis is a tool for reducing model uncertainty by identifying how the variance of inputs contributes to the outcome of ABMs and discrepancies between outcomes and observed data (Kang et al, 2022;Kang & Aldstadt, 2019;Ligmann-Zielinska, 2013;Saltelli et al, 1999). In this study, we employed an ML emulator outputs of simulations to reduce computational intensity of sensitivity analysis (Chen et al, 2021;Ligmann-Zielinska et al, 2020). To approximate our simulation model, we used linear, ridge, and lasso regression models to fit the results.…”
Section: Sensitivity Analysis With Emulator Modelmentioning
confidence: 99%
“…It’s not the first time that an artificial neural network is used to build a metamodel of an ABM. For example, in [41], we showed that a fully dense neural network was capable of reproducing the ABM population curves for Pantoea . What is novel about using a metamodel based on a RNN is the fact that with such a metamodel one can reproduce ABM synthetic images of growth.…”
Section: Discussionmentioning
confidence: 99%
“…ABM is a powerful simulation technique that characterizes a complex dynamic system through its interacting entities [1][2][3]. While ABM provides extensive flexibility for various applications, the complexity of real-world models necessitates the intensive use of computing resources and significant computational time.…”
Section: Introductionmentioning
confidence: 99%